A Comprehensive 10-Year Nationwide Pharmacovigilance Surveillance on Antibacterial Agents in Korea: Data Mining for Signal Detection of Trends and Seriousness of Adverse Events - Seon Hu Mo; Soo Hyeon Lee; Chang-Young Choi; Yongjun Sunwoo; Sooyoung Shin; Yeo Jin Choi (Microorganisms)
A comprehensive pharmacovigilance surveillance on antibacterials is lacking. This study aims to investigate safety signals of antibacterial-related adverse drug events (ADEs) with seriousness and to identify predictors of serious ADEs. This study investigated 52,503 antibacterial-induced ADEs reported to the Korea Adverse Event Reporting System Database from January 2013 to December 2022. Disproportionality analysis was conducted, and the effect sizes were estimated by reporting odds ratios (ROR), proportional reporting ratio (PRR), and information component (IC). Multivariate logistic regression was performed to investigate the predictors of serious ADEs by estimating the odds ratio (OR). Serious events were more likely to be cardiovascular disorders (ROR 6.77, PRR 6.6, IC 2.37), urinary system disorders (ROR 5.56, PRR 5.22, IC 2.12), and platelet, bleeding, and clotting disorders (ROR 5.41, PRR 5.17, IC 2.06). The predictors may include age (OR 1.05), the number of concomitant medications (OR 1.44), concomitant proton pump inhibitors (OR 1.46) and non-steroidal anti-inflammatory drugs (OR 1.38) use, and specific antibacterial classes, while multiple antibacterial therapy was associated with lower serious ADE risks. The sensitivity analysis also suggests the male sex (OR 1.18) as a potential predictor of serious ADEs. However, further studies are imperative to determine the causality of antibacterial-induced ADEs in critically ill patients.